Enzymatic Synthesis of 2‐Deoxyribose 1‐Phosphate and Ribose 1 Phosphate and Subsequent Preparation of Nucleosides. Issue 41 (24th October 2019) - Kulikova, Irina V.; Drenichev, Mikhail S.; Solyev, Pavel N.; Alexeev, Cyril S.; Mikhailov, Sergey N.
Abstract : α‐Ribose‐1‐phosphate (Rib‐p) and 2‐deoxy‐α‐ribose‐1‐phosphate (dRib‐p) are key intermediates in nucleoside metabolism and are important starting compounds for the enzymatic synthesis of various modified nucleosides. To date, chemical and enzymatic methods allowed the preparation of these compounds in rather low yields (11–37 %). This prevents their widespread use for the enzymatic synthesis of biologically active and practically important nucleosides. Here we propose to use 7‐methyl‐2′‐deoxyguanosine (7‐Me‐dGuo) and 7‐methylguanosine (7‐Me‐Guo) for the preparation of dRib‐p and Rib‐p. In this paper, we present the effective preparation of Rib‐p and dRib‐p starting from readily prepared 7‐methylguanosine derivatives via their irreversible enzymatic phosphorolysis in the presence of purine nucleoside phosphorylase. Rib‐p and dRib‐P are obtained in nearly quantitative yields (HPLC analysis) and 74–96 % yields after their isolation and purification, which is much higher than previously reported. Abstract : We present a novel enzymatic method for the preparation of Rib‐p and dRib‐p starting from 7‐Me‐Guo and 7‐Me‐dGuo. Practically irreversible phosphorolysis of 7‐Me‐Guo and 7‐Me‐dGuo in the presence of PNP ensures the quantitative transformation of starting nucleosides to anomerically pure α‐Rib‐p and α‐dRib‐p. Rib‐p and dRib‐p are obtained with 74–96 % yields after isolation and purification.